PELATIHAN BRANDING, DESAIN KEMASAN DAN PEMASARAN DIGITAL GUNA MENINGKATKAN DAYA SAING UMKM SANTAN KELAPA - Dorie P. Kesuma; Lisa Amelia Fransen; Daniel Udjulawa; Ery Hartati (Universitas Multi Data Palembang, Fakultas Ilmu Komputer dan Rekayasa, 2026)
The Erni Susilo coconut milk processing Micro, Small, and Medium Enterprise, located in Kemuning District, faces challenges regarding low competitiveness compared to similar products. This issue stems from ineffective brand identity management, simple packaging design, and suboptimal digital marketing. This community service project aims to improve the business quality of the owner through training in brand identity, packaging design, and digital marketing. The methodology employs a participatory approach, including focus group discussions, counseling, practical training, and mentoring. Results indicate an increase in the participant's understanding of the importance of brand identity, the ability to design more attractive packaging, and the skills to utilize social media for promotion. In conclusion, the training approach successfully improved the entrepreneur's knowledge and skills in utilizing technology to develop the business, thereby encouraging potential sales growth in the future.